Stem Cell Therapy for Diabetes: Beta Cells versus Pancreatic Progenitors - Bushra Memon (4792767) (2020)
Diabetes mellitus (DM) is one of the most prevalent metabolic disorders. In order to replace the function of the destroyed pancreatic beta cells in diabetes, islet transplantation is the most widely practiced treatment. However, it has several limitations. As an alternative approach, human pluripotent stem cells (hPSCs) can provide an unlimited source of pancreatic cells that have the ability to secrete insulin in response to a high blood glucose level. However, the determination of the appropriate pancreatic lineage candidate for the purpose of cell therapy for the treatment of diabetes is still debated. While hPSC-derived beta cells are perceived as the ultimate candidate, their efficiency needs further improvement in order to obtain a sufficient number of glucose responsive beta cells for transplantation therapy. On the other hand, hPSC-derived pancreatic progenitors can be efficiently generated in vitro and can further mature into glucose responsive beta cells in vivo after transplantation. Herein, we discuss the advantages and predicted challenges associated with the use of each of the two pancreatic lineage products for diabetes cell therapy. Furthermore, we address the co-generation of functionally relevant islet cell subpopulations and structural properties contributing to the glucose responsiveness of beta cells, as well as the available encapsulation technology for these cells. Other Information Published in: Cells License: https://creativecommons.org/licenses/by/4.0/ See article on publisher's website: https://dx.doi.org/10.3390/cells9020283